Manajemen Pengembangan Kurikulum Pendidikan Madrasah Dalam Mewujudkan Madrasah Bermartabat di MTS Lab UINSU - Chairunnisa Sagala; Zainur Rozzaqiyah; Rosa Marshanda; Desmawati Ramadhani; Yogi Andrian; Inom Nasution; Maryono M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The curriculum is a component that plays a strategic role in the success of the education and learning process in order to achieve institutional goals in educational institutions. Therefore, the curriculum system greatly determines the success or failure of a madrasah/school in becoming a quality and quality educational institution. Ahmad Tafsir explained that the curriculum contains four components, namely objectives, content, teaching and learning methods or processes, and evaluation. The four components in the curriculum are related to each other. Implementation of the curriculum is divided into two parts, namely the implementation of the curriculum at the madrasah/school level and class level. Between the school curriculum and the class curriculum is the basis of the learning process which is the main guideline for the implementation of education in an educational institution. At the madrasah/school level, a school principal is the main person in charge, while the teacher acts as the spearhead of implementing the curriculum at the classroom level. This study seeks to provide an overview of the importance of curriculum development at the madrasah level so that it can become the main guideline and reference in implementing learning so as to create an optimal and superior learning atmosphere.